Nutritional, Sensory, and Glycemic Characterization of Functional Noodles Substituted with Beneng Taro, Red Beans, and Moringa Leaves - Rakhmi Setyani Sartika; Annisa Nuradhiani; Rahmawati Rahmawati; Sifa Nurani; Fachruddin Perdana; Ratu Diah Koerniawati (Journal of Health and Nutrition Research, 2026)
The increasing trend of consuming ultra-processed foods, such as instant noodles, necessitates the development of healthier and more functional food alternatives. This study aimed to develop functional dry noodles by partially substituting wheat flour with local Banten ingredients: Beneng taro, red beans, and Moringa leaves. The experiment utilized a completely randomized design (CRD) with three substitution treatment levels (F1, F2, F3) replicated three times. The nutritional quality of each formula was determined through proximate analysis and dietary fiber content. Sensory quality was assessed using hedonic and quality hedonic tests involving 30 semi-trained panelists. The selected formula was determined through a combined scoring of nutritional and sensory analysis results, followed by Glycemic Index (GI) testing. Based on the scoring, Formula F3 with a ratio of wheat flour : taro flour : red bean flour : moringa leaf flour : taro starch, namely F3 (50 g:17.5 g:17.5 g:5 g:10 g) was selected as the optimal formula, containing per 100g: 389.98 kcal energy, 13.52 g protein, 4.06 g fat, 60.93 g carbohydrate, and 11.08 g dietary fiber. Sensory evaluation showed that panelists liked the color and aroma parameters of F3, and slightly liked the texture, taste, and overall attributes. F3 meets the nutrition label claims as a "source of protein" (22.53% ALG - Acuan Label Gizi/Nutrition Label Reference) and "high in fiber" (36.93% ALG). Furthermore, F3 yielded a Glycemic Index of 62.19 (medium category) with a Glycemic Load of 18.94 (medium category). Thus, this functional dry noodle product has the potential to be a healthy food alternative, serving as a source of protein and high in fiber, while exhibiting a controlled glycemic response.